2002
DOI: 10.1080/10915810252826000
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation Toxicology of Octamethylcyclotetrasiloxane (D4) Following a 3-Month Nose-Only Exposure in Fischer 344 Rats

Abstract: Octamethylcyclotetrasiloxane (D4) is a low-molecular-weight cyclic siloxane used primarily in the synthesis of silicone polymers. The objective of the present study was to evaluate the subchronic toxicity of D4 following a 3-month nose-only inhalation exposure. Male and female Fischer 344 rats (20/sex/group) were exposed 6 h/day, 5 days/week for 3 months to vapor concentrations of 0, 35, 122, 488, and 898 ppm D4. Also, an additional 10 per sex in the control and high-exposure groups were allowed a 4-week recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 40 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…Several studies have reported toxicity, especially reproductive and endocrine effects, of siloxanes in laboratory animals (Burns-Naas et al, 1998;Burn-Naas et al, 2002;McKim et al, 2001;He et al, 2003;Meeks et al, 2007;Quinn et al, 2007a,b;Siddiqui et al, 2007). A risk assessment conducted in Canada indicated that D5 met the criteria for persistence (Environment Canada, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…Several studies have reported toxicity, especially reproductive and endocrine effects, of siloxanes in laboratory animals (Burns-Naas et al, 1998;Burn-Naas et al, 2002;McKim et al, 2001;He et al, 2003;Meeks et al, 2007;Quinn et al, 2007a,b;Siddiqui et al, 2007). A risk assessment conducted in Canada indicated that D5 met the criteria for persistence (Environment Canada, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…Liver weight increase was reversible in males, but not in females. The NOAEL was ≥700 ppm (>8.49 mg/L, measured) on the basis that the liver weight changes were adaptive and not toxicological in nature (Burns-Naas and Meeks, 2002). A study of similar design but using lower concentrations was also conducted.…”
Section: Animal Toxicity Datamentioning
confidence: 99%
“…However, lower exposure concentrations (35 ppm, 122 ppm, and 488 ppm) did not elicit these same effects. 120…”
Section: Chemistrymentioning
confidence: 99%
“…A separate group of rats (6 males and 6 females), cannulated via jugular vein, was used to determine radioactivity and parent D 6 concentration in the blood at 15 minutes and at 1,6,12,18,24,48,72,96,120,144, and 168 hours postdosing. Wholebody autoradiography (WBA) was used for qualitative in vivo assessment of tissue distribution of radioactivity in male and female rats after single oral administration of D 6 (in corn oil).…”
Section: Absorption Distribution Metabolism and Excretionmentioning
confidence: 99%